Tinjauan Ontologi Seni - Tissa Tavini (JPKS (Jurnal Pendidikan dan Kajian Seni), 2020)
Abstract : Art is one subsdivision of science that very close to the praxis dimension. Art is also associated with practical things, so the orientation of art is not released from something related to the conception of art creation itself. So the some society sometimes does not conduct an ontological review of the nature and existence of art. This ontological review is often overlooked, because the orientation of  art is only associated with practical things. The construction of ontological review is important to be able understanding the innermost nature of art and also be aware of the presence of art itself. When the conceptual construction of the deepest nature and presence of art can be understood radically, comprehensively, and systematically it will certainly have an impact on the construction of understanding and awareness about art. So that the implementation of art does not only stop at the praxis dimension but it goes even deeper, namely to the deepest nature of the art itself and also will bring the presence of art into the midst of wisdom. Keywords: ontology, nature, existence, art  Abstrak :  Seni merupakan salah satu cabang ilmu yang sangat dekat dengan dimensi praksis. Seni sering selalu dikaitkan dengan hal-hal yang praktikal, sehingga orientasi mengenai seni tidak luput dari sesuatu yang berkaitan dengan konsepsi penciptaan seni saja. Maka sering kali masyarakat tidak melakukan tinjauan ontologis mengenai hakikat dan keberadaan mengenai seni. Tinjauan ontologis ini sering kali terabaikan, karena orientasi mengenai seni hanya dikaitkan dengan hal-hal praksis. Konstruksi mengenai tinjauan ontologis merupakan hal yang cukup penting agar mampu memahami hakikat terdalam dari seni dan juga menyadari kehadiran dari seni itu sendiri. Ketika konstruksi konseptual mengenai hakikat terdalam dan kehadiran seni dapat dipahami secara radikal, komprehensif, dan sistematis tentunya akan berdampak pada konstruksi pemahaman dan kesadaran mengenai seni. Sehingga implementasi seni tidak hanya berhenti pada dimensi praksis akan tetapi jauh lebih dalam lagi, yaitu hingga ke hakikat terdalam dari seni itu sendiri dan juga akan membawa kehadiran seni ke tengah-tengah kebijaksanaan. Kata kunci: ontologi, hakikat, keberadaan, seni